Progress in the research of genetics and clinical manifestation of paroxysmal kinesigenic dyskinesia - Xiao-jun HUANG; Li CAO; Sheng-di CHEN (Chinese Journal of Contemporary Neurology and Neurosurgery, 2013)
Paroxysmal kinesigenic dyskinesia (PKD) is a disorder characterized by recurrent and brief attacks that are induced by sudden voluntary movement with highly clinical and genetic heterogeneity. Familial PKD are mostly autosomal dominant inherited and proline-rich transmembrare protein 2 (PRRT2) gene has been identified as the causative gene for PKD. So far 56 mutations have been documented and most of them are nonsense ones. No obvious genotype-phenotype correlation has been observed and the function of PRRT2 is still unclear, but the interaction between PRRT2 and synaptosomal-associated protein 25 (SNAP25) will shed the light on the research of PKD mechanism.